The use of individualized speed and intensity thresholds for determining the distance run at high-intensity in professional soccer - Abt, G.; Lovell, R. (Journal of Sports Sciences, 2009)
As with other match analysis systems, ProZone® uses an absolute speed threshold to identify running speeds at "high-intensity". In this study, we examined the use of an individualized high-intensity speed threshold based on the speed at the second ventilatory threshold (VT2speed) for assessment of the distance run at high-intensity during matches. Ten professional soccer players completed a maximal treadmill test to determine VT2speed. Match data were identified by means of the ProZone® match analysis system. The distances run at high-intensity during matches were calculated using the default value (19.8 km/h) and VT2speed. Differences between VT2speed and the default were analysed using a non-parametric median sign test. The distances run at high-intensity were compared with a paired t-test. The median VT2speed was 15 km/h (range 14-16 km/h), which was less than the default (P < 0.01). Mean distance un at high-intensity based on the default and VT2speed was 845 m (s = 296) and 2258 m (s = 707), respectively [mean difference 1413 m; P < 0.001 (95% CI: 1037-1789 m)]. The high-intensity running speeds based on the second ventilatory threshold are substantially less than that used as the default within the ProZone® match analysis system, thus the distance run at high-intensity can be substantially underestimated.